Performance characteristics of an instrument-free point-of-care CD4 test (VISITECT®CD4) for use in resource-limited settings. Issue 9 (September 2020) - Vidhyavathi, Vairamohan; Iqbal, Hussain Syed; Kanthamani, Kannaiyan; Solomon, Sunil Suhas; Nandagopal, Paneerselvam; Luchters, Stanley; Pham, Minh D.; Forbes, James; Crowe, Suzanne M.; McMurran, Christopher; Anderson, David A.; Balakrishnan, Pachamuthu
Objective: CD4+ T lymphocyte count remains the most common biomarker of immune status and disease progression in human immunodeficiency virus (HIV)-positive individuals. VISITECT®CD4 is an instrument-free, low-cost point-of-care CD4 test with a cut-off of 350 CD4 cells/μL. This study aimed to evaluate VISITECT®CD4 test's diagnostic accuracy. Methods: Two hundred HIV-positive patients attending a tertiary HIV centre in South India were recruited. Patients provided venous blood for reference and VISITECT®CD4 tests. An additional finger-prick blood sample was obtained for VISITECT®CD4. VISITECT®CD4's diagnostic performance in identifying individuals with CD4 counts ≤350 cells/μL was assessed by calculating sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) taking flow cytometry as the reference. Results: The overall agreement between VISITECT®CD4 and flow cytometry was 89.5% using venous blood and 81.5% using finger-prick blood. VISITECT®CD4 showed better performance using venous blood [sensitivity: 96.6% (95% confidence interval: 92.1%–98.9%), specificity: 70.9% (57.1%–82.4%), PPV: 89.7% (83.9%–94.0%) and NPV: 88.6% (75.4%–96.2%)] than using finger-prick blood [sensitivity: 84.8% (77.9%–90.2%), specificity: 72.7% (59.0%–83.9%), PPV: 89.1% (82.7%–93.8%) and NPV: 64.5% (51.3%–76.3%)]. Conclusion: VISITECT®CD4 performed well using venous blood, demonstrating its potential utility in decentralization of CD4 testing services in resource-constrained settings.